Determination Of The Amino Acid And Chemical Composition Of Canned Smoked Mussels (Mytilus Galloprovincialis, L.) - Sengoer, Guelguen F.; Guen, Hueseyin; Kalafatoglu, Hanife (Aperta, 2008)
In this research smoking and canning techniques were applied to cultured mussels (Mytilus galloprovincialis, L.) from the Canakkkale Strait in Eceabat, Turkey. Mussels that were smoked by liquid and traditional methods were canned in different sauces. The chemical composition and amino acid composition of the canned smoked mussels were determined by the results of laboratory analyses. As a result of smoking and canning mussels, a food with high nutritional value was obtained. It was determined that the heat applied to the product during smoking and canning did not effect amino acid composition negatively and that if any losses occur, they may be replaced by the sauce contents.